TRAINING MAKING A DIGITAL POSTER USING THE CANVA APP IN CREATING PROCEDURE TEXT AT PKBM KATIMPUN - Maida Norahmi; Muhammad Affandi; Erma Sujiyani; Novi Widiastuti (IKIP Siliwangi Bandung, 2023)
Community Learning Center is a non-governmental organization formed by and for the community that is engaged in learning and is located at the village or sub-district level. To equal education, PKBM has a strategic function to serve all school-age children or people who want to go to school but are unable to attend school. Like others, PKBM Katimpun has also carried out its function to serve and provide education for the surrounding community. The presence of PKBM is a forum for carrying out various educational activities that are equivalent to formal schools in general. The problems faced by PKBM Katimpun are the need to increase expertise in the field of technology and information so that students can compete in the work field later. In addition, students also need to improve their academic abilities. In this case, English lessons are one of the subjects that contribute to the development of skills for students in their future work. Therefore, we took the initiative to combine these two targets into one training material which is expected to improve skills in IT as well as the ability to learn and write English texts. This community service activity is intended to provide training to PKBM Katimpun students through two materials, namely the use of the Canva application and learning to write procedure texts in English.